Positive psychology as a strategy for promoting sustainable population policies - Alon Tal (Heliyon, 2020)
Demographic stability constitutes a paramount global environmental objective. Yet, decades of efforts, highlighting the perils of overpopulation, have failed to slow the rapid global population growth. In considering an alternative strategy, insights from the field of positive psychology are explored for their potential to inform future demographic policies. After briefly reviewing sustainable advocacy efforts, different theories behind individual fertility decisions are presented. Following, key components of prominent successful family planning interventions are analysed using a ‘positive psychology’ perspective. Three ‘positive psychology’ strategies are explored for their potential to inform sustainable population: a “direct” approach that emphasizes individual benefits rather than indirect gains through mitigation of damages; an emphasis on the convergence between the collective and individual benefits of two--child families; and application of behavioral change theories in demographic policies to better facilitate sustainable individual fertility decisions. The paper posits that a positive psychology conceptualization offers a promising way to re-think the design of demographic policies and frame sustainable population interventions.